Theology and philosophy within Radical Orthodoxy (Milbank) and Reformational Philosophy (Dooyeweerd) - D. Strauss (Acta Theologica)
This article aims to show that, despite agreeing on some basic issues such as rejecting the dogma of the autonomy of reason and accepting that there is no territory independent of God, Radical Orthodoxy and Reformational Philosophy nonetheless differ. While both philosophy and theology, according to Radical Orthodoxy, investigate being qua, being only theology has the task to relate being to God. This view still continues the medieval nature?grace split. Alternatively, it is argued that the distinctive feature of scholarly endeavours, namely modal abstraction, may enhance an appreciation of the special scientific nature of theology, without advocating a “static division of human life” into “distinct spheres”.